Genetic and environmental factors affecting ultrasound measures of longissimus muscle area and backfat thickness in Nelore cattle - Yokoo, M. J. [UNESP]; Albuquerque, Lucia Galvão de [UNESP]; Lobo, R. B.; Bezerra, L. A. F.; Araujo, F. R. C.; Silva, J. A. V. [UNESP]; Sainz, R. D. (Elsevier B.V., 2008)
The aim of the present study was to evaluate the genetic and environmental factors affecting records of longissimus muscle area (LMA) and back fat thickness (BF) obtained between the 12th and 13th ribs, and rump fat thickness (RF) between the hook and pin bones, measured by real-time ultrasound in Nelore cattle. Also, weight records of 22,778 animals born from 1998 to 2003, in ten farms across six Brazilian states were used. Carcass traits as measured by ultrasound of the live animal were recorded from 2002 to 2004 in 2590 males and females with ages varying from 450 to 599 days. Fixed models including farm, year and season of birth, sex and type of feed effects, and the covariates age of dam (AOD) and age of animal at measurement were used to study the effect of environmental factors on these traits. The genetic parameters for LMA, BF and RF were estimated with two and three-trait animal models with 120-day weights using a restricted maximum likelihood method. All environmental effects significantly affected carcass traits, with the exception of year of birth for BF and RF and AOD for LMA. The heritability estimates for LMA, BF and RF were 0.35, 0.51 and 0.39, respectively. Standard errors obtained in one-trait analyses were from 0.07 to 0.09. Genetic correlation estimates between LMA and the two traits of subcutaneous fat were low (close to zero) and 0.74 between BF and RF, indicating that the selection for LMA should not cause antagonism in the genetic improvement of subcutaneous fat measured by real-time ultrasound. (C) 2007 Elsevier B.V. All fights reserved.
Keywords: age of dam; Carcass traits; compensatory growth; Genetic correlation; Heritability; Rump fat thickness